2016
DOI: 10.1089/end.2016.0113
|View full text |Cite
|
Sign up to set email alerts
|

Tamsulosin or Silodosin Adjuvant Treatment Is Ineffective in Improving Shockwave Lithotripsy Outcome: A Short-Term Follow-Up Randomized, Placebo-Controlled Study

Abstract: Tamsulosin and silodosin are ineffective in increasing stone-free rate as well as early patients' discomfort after extracorporeal lithotripsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the present randomized nonplacebo-controlled study, the results did not show a significant difference in the stonefree rate after a single ESWL session between the patients treated with tamsulosin and the patients in the control group (53.57% vs. 48.27%; p � 0.680) over eight weeks for patients with a single renal stone (located in the renal pelvis, upper calix, or middle calix) and with the stone size between 5 and 20 (mm) in diameter. We observed results similar to those described by De Nunzio et al [17], who identified 58% stonefree rate in the tamsulosin group, 47% in the silodosin group, and 55% in the control group, with no statistically significant difference (p � 0.399) between patients treated over 21 days after a single ESWL session. In concordance, Ahmed et al [18] also did not find a significant difference in the stone-free rate between patients in the tamsulosin group and the control group (78% vs. 69%, respectively, p � 0.108) in an up to 12-week study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present randomized nonplacebo-controlled study, the results did not show a significant difference in the stonefree rate after a single ESWL session between the patients treated with tamsulosin and the patients in the control group (53.57% vs. 48.27%; p � 0.680) over eight weeks for patients with a single renal stone (located in the renal pelvis, upper calix, or middle calix) and with the stone size between 5 and 20 (mm) in diameter. We observed results similar to those described by De Nunzio et al [17], who identified 58% stonefree rate in the tamsulosin group, 47% in the silodosin group, and 55% in the control group, with no statistically significant difference (p � 0.399) between patients treated over 21 days after a single ESWL session. In concordance, Ahmed et al [18] also did not find a significant difference in the stone-free rate between patients in the tamsulosin group and the control group (78% vs. 69%, respectively, p � 0.108) in an up to 12-week study.…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies reported different complication-rate values. De Nunzio et al [ 17 ] reported that 20% (12 of 60) of the patients had complications; 11 of them presented with acute pain requiring only analgesic treatment, and one patient underwent an additional procedure (ureteroscopy). The authors reported a statistically significant difference in the complication rate in favor of the tamsulosin group ( p = 0.008).…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study is that a placebo arm was not considered because sufficient evidence to support the use of tamsulosin as an adjunct to SWL exists [4,7,25]. However, as there are conflicting results from previous studies, a placebo arm might have added value [26]. In addition, according to Roehrborn et al [16], a clinically significant effect of tadalafil 5 mg is usually seen to be as effective as 10 and 20 mg at 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, there were 21 RCTs [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], covering 1445 patients and 1478 controls. Patient demographics are detailed in Table 1, whilst lithotripter/stone free definitions are detailed in Table 2.…”
Section: Demographics Of Included Studiesmentioning
confidence: 99%